Violaxanthin inhibits nonphotochemical quenching in light‐harvesting antenna of Chromera velia. Issue 8 (4th April 2016) - Kaňa, Radek; Kotabová, Eva; Kopečná, Jana; Trsková, Eliška; Belgio, Erica; Sobotka, Roman; Ruban, Alexander V.
Abstract : Non‐photochemical quenching (NPQ) is a photoprotective mechanism in light‐harvesting antennae. NPQ is triggered by chloroplast thylakoid lumen acidification and is accompanied by violaxanthin de‐epoxidation to zeaxanthin, which further stimulates NPQ. In the present study, we show that violaxanthin can act in the opposite direction to zeaxanthin because an increase in the concentration of violaxanthin reduced NPQ in the light‐harvesting antennae of Chromera velia . The correlation overlapped with a similar relationship between violaxanthin and NPQ as observed in isolated higher plant light‐harvesting complex II. The data suggest that violaxanthin in C. velia can act as an inhibitor of NPQ, indicating that violaxanthin has to be removed from the vicinity of the protein to reach maximal NPQ. Abstract : High violaxanthin results in low non‐photochemical quenching (NPQ) in Chromera velia antenna complexes. Violaxanthin has an antagonistic effect for NPQ in comparison to zeaxanthin. High NPQ requires the removal of violaxanthin from the vicinity of the protein.